Choose the equivalent system of linear equations that will produce the same solution as the one given below.

4x − y = −11
2x + 3y = 5


Option 1)−4x − 9y = −21
−10y = −30

Option 2)4x + 3y = 5
2y = −6

Option 3)7x − 3y = −11
9x = −6

Option 4)12x − 3y = −33
14x = −28

Respuesta :

Greetings!

Answer:

Option 4

Step-by-step explanation:

Firstly, we need to make the two x's or the two y numbers the same. Lets multiply the second equation by 2:

(2x + 3y = 5 ) * 2 =

4x + 6y = 10

Now, subtract the second equation from the first one:

(4x - y = -11) - (4x + 6y = 10)

4x - 4x = 0

-y - 6y = -7y

-11 - 10 = -21

-7y = -21

Divide both sides by -7:

y = 3

Plug 3 into the first equation as y:

4x - 3 = -11

4x = -11 + 3

4x = -8

x = -2

So x = -2 and y = 3. We need to find one of the options that equals this.


Option  1)

-4x - 9y = -21

-10y = -30

40x - 90y = -210

-90y = -270

40x - 0 = 40x

-90y - - 90y = -90 + 90 = 0y

-210 - -270 = -210 + 270 = 60

40x = 60

x = 1.5

We already know this isn't equivalent because the x value is not the x value of the given equation.


Option 2)

4x + 3y = 5

2y = -6

_______

8x + 6y = 10

6y = -18

8x - 0 = 8x

6y - 6y = 0

10 - -18 = 10 + 18 = 28

8x = 28

x = 3.5

So we know this isn't equivalent because again, the x value isn't the same as the given equation.


Option 3

7x - 3y = -11

9x = -6

-----------

63x - 27y = -99

63x = -42

----------------

63x - 63x = 0

-27y - 0 = -27y

-99 - - 42 = -99 + 42 = -57

-27y = -57

-9y = -19

9y = 19

y = 19/9

So we know this one isn't equivalent as the y value isn't the same as the given equation.


Option 4

12x - 3y = -33

14x = -28

x = -28/14 = -2

12(-2) - 3y = -33

-24 - 3y = -33

-3y = -33 + 24

-3y = -9

y = 9/3

y = 3

So x = -2 and y = -3 which is the same as the first equation.


Hope this helps!

ACCESS MORE